Alif: Journal of Comparative Poetics (jstor)
Alif is a refereed multilingual journal appearing annually in the spring. It presents scholarly articles in Arabic, English and occasionally French. Each issue is dedicated to a specific theme. Its multidisciplinary nature allows different traditions and languages to confront and complement each other in its pages.
Keywords: Middle East Studies